2023
DOI: 10.1002/adma.202209906
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Stretchable Organic Electrochemical Transistors for Physiological Sensing Devices

Abstract: Flexible and stretchable bioelectronics provides a biocompatible interface between electronics and biological systems and has received tremendous attention for in situ monitoring of various biological systems. Considerable progress in organic electronics has made organic semiconductors, as well as other organic electronic materials, ideal candidates for developing wearable, implantable, and biocompatible electronic circuits due to their potential mechanical compliance and biocompatibility. Organic electrochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 314 publications
0
25
0
1
Order By: Relevance
“…Fibrous OECT has also been developed to directly diagnose metabolites (e.g., sweat, dopamine, potassium ions, glucose, and lactate). [ 233–239 ] Wang et al. designed a fiber OECT by polymerizing PPy nanowire on rGO‐coated PA fiber, which achieved a sensitivity of 0.773 NCR per decade over a wide range of 1 n m to 5 µ m .…”
Section: Application Of Textile Optoelectronics‐integrated Logic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibrous OECT has also been developed to directly diagnose metabolites (e.g., sweat, dopamine, potassium ions, glucose, and lactate). [ 233–239 ] Wang et al. designed a fiber OECT by polymerizing PPy nanowire on rGO‐coated PA fiber, which achieved a sensitivity of 0.773 NCR per decade over a wide range of 1 n m to 5 µ m .…”
Section: Application Of Textile Optoelectronics‐integrated Logic Systemsmentioning
confidence: 99%
“…[232] Fibrous OECT has also been developed to directly diagnose metabolites (e.g., sweat, dopamine, potassium ions, glucose, and lactate). [233][234][235][236][237][238][239] Wang et al designed a fiber OECT by polymerizing PPy nanowire on rGO-coated PA fiber, which achieved a sensitivity of 0.773 NCR per decade over a wide range of 1 nm to 5 μm. [240] Wu et al demonstrated a CNT-fiber-based OECT using PEDOT:PSS as an active layer, achieving biochemical detection of H 2 O 2 , glucose, dopamine, and glutamate.…”
Section: Bio-signal Recordingmentioning
confidence: 99%
“…Because of such a strain distribution, only a limited uniform structural color control can be realized during the stretching tuning process, even if multi-pixel-arrayed photonic structures are used. [26,45] Also, it should be noted that this strain distribution is problematic not only in mechanochromic structural colors, but also in most multi-pixel requiring stretchable technologies [46,47] as well. Shortly, switching uniformity in multi-pixel operations is a major technical challenge in most stretchable technologies for practical uses.…”
Section: Introductionmentioning
confidence: 99%
“…Organic and polymeric semiconductors have gained widespread attention owing to their unique advantages of being lightweight, excellent mechanical trait and solution processability, which has led to various applications in organic electronic devices, such as organic solar cells (OSCs), organic thin-film transistors (OTFTs), organic thermoelectrics (OTEs), and organic electrochemical transistors (OECTs). [1][2][3][4][5] Organic and polymeric semiconductors can be divided into p-type and n-type ones based on the charge carrier polarity. Over the past few decades, p-type organic semiconductors have achieved great success in terms of material diversity and device performance.…”
Section: Introductionmentioning
confidence: 99%